2014
DOI: 10.1261/rna.046300.114
|View full text |Cite
|
Sign up to set email alerts
|

The capacity of target silencing by Drosophila PIWI and piRNAs

Abstract: Although Piwi proteins and Piwi-interacting RNAs (piRNAs) genetically repress transposable elements (TEs), it is unclear how the highly diverse piRNA populations direct Piwi proteins to silence TE targets without silencing the entire transcriptome. To determine the capacity of piRNA-mediated silencing, we introduced reporter genes into Drosophila OSS cells, which express microRNAs (miRNAs) and piRNAs, and compared the Piwi pathway to the Argonaute pathway in gene regulation. Reporter constructs containing seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
93
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 61 publications
9
93
0
Order By: Relevance
“…In agreement with the study by Lau and colleagues (Post et al 2014), we found that recruitment of Piwi to a reporter construct via a sequence stretch complementary to endogenous piRNAs elicits potent reporter silencing in a Piwi-dependent and target orientation-dependent manner (Supplemental Fig. S1A).…”
Section: Recruitment Of Cg9754 To Rna or Dna Elicits Potent Transcripsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with the study by Lau and colleagues (Post et al 2014), we found that recruitment of Piwi to a reporter construct via a sequence stretch complementary to endogenous piRNAs elicits potent reporter silencing in a Piwi-dependent and target orientation-dependent manner (Supplemental Fig. S1A).…”
Section: Recruitment Of Cg9754 To Rna or Dna Elicits Potent Transcripsupporting
confidence: 92%
“…Several studies indicate that binding of the Piwi-piRNA complex to a nascent target RNA causes heterochromatin formation and transcriptional silencing (e.g., Sarot et al 2004;Sienski et al 2012;Le Thomas et al 2013;Post et al 2014). In agreement with the study by Lau and colleagues (Post et al 2014), we found that recruitment of Piwi to a reporter construct via a sequence stretch complementary to endogenous piRNAs elicits potent reporter silencing in a Piwi-dependent and target orientation-dependent manner (Supplemental Fig.…”
Section: Recruitment Of Cg9754 To Rna or Dna Elicits Potent Transcripsupporting
confidence: 91%
See 2 more Smart Citations
“…S3B,C). Although other regulation patterns in the cytoplasm and nucleoplasm were more complicated, the up-regulated nascent RNA changes suggested a transcriptional gene silencing mechanism, which is discussed in greater detail below as well as tested in a second study (Post et al 2014).…”
Section: Recovery Of Te Transcripts Confirms Approach To Identify Piwmentioning
confidence: 95%